Capturing CO2 to reversible ionic liquids for dissolution pretreatment of cellulose towards enhanced enzymatic hydrolysis. (15th January 2019) - Li, Xiang; Xu, Qinqin; Shen, Hongwei; Guo, Yuanlong; Wu, Mouyi; Peng, Ya; Zhang, Lihua; Zhao, Zongbao Kent; Liu, Yu; Xie, Haibo
Graphical abstract: TMG-EG-DMSO mixed organic liquids after absorption of CO2 can be used as an efficient and recyclable solvent for the dissolution pretreatment of cellulose for enhanced enzymatic saccharification, and the identified structural rearrangements arose by the dissolution pretreatment by WXRD, FT-IR, SEM and AFM in terms of crystalline structure and surface morphology results in the good performance. Highlights: Organic liquids absorbing CO2 can dissolve up to 10 wt% cellulose. The pretreated cellulose can be fully hydrolyzed to glucose by enzyme. Significantly structural rearrangements of cellulose results in the good performance. The solvent system can be easily recycled and reused without loss of performance. Abstract: To overcome the natural recalcitrance of cellulose for glucose production in aqueous media catalyzed by enzyme, in this study, a dissolution pretreatment strategy was developed by using in situ formed CO2 -based reversible ionic compounds (RICs)/DMSO mixed organic electrolytes under mild conditions. The influences of the constitution of RICs, CO2 pressure, dissolution pretreatment time on the physic-chemical structure of cellulose were investigated systematically by FTIR, XRD, SEM, AFM towards in-depth understanding of the correlations between the pretreatment conditions, micro-scale structure and enzymatic saccharification of cellulose. The results showed that the tetramethyl guanidine (TMG) based RICs solvent system [TMGH]2 + [O2 COCH2 CH2 OCO2 ] 2− /DMSO (XRICs = 0.1, XRICs : the mole fraction of the formed RICs in the mixture) presented the best performance, which was evidenced by 100% glucose yield after the dissolution-regeneration pretreatment strategy under mild conditions (T = 60 °C, Pco2 = 2.0 MPa, t = 2 h). Furthermore, the solvent system have good recyclability and usability.